Cutaneous Leishmaniasis: The Complexity of Host’s Effective Immune Response against a Polymorphic Parasitic Disease - Áurea Gabriel; Ana Valério-Bolas; Joana Palma-Marques; Patrícia Mourata-Gonçalves; Pedro Ruas; Tatiana Dias-Guerreiro; Gabriela Santos-Gomes (Journal of Immunology Research)
This review is aimed at providing a comprehensive outline of the immune response displayed against cutaneous leishmaniasis (CL), the more common zoonotic infection caused by protozoan parasites of the genus Leishmania. Although of polymorphic clinical presentation, classically CL is characterized by leishmaniotic lesions on the face and extremities of the patients, which can be ulcerative, and even after healing can lead to permanent injuries and disfigurement, affecting significantly their psychological, social, and economic well-being. According a report released by the World Health Organization, the disability-adjusted life years (DALYs) lost due to leishmaniasis are close to 2.4 million, annually there are 1.0–1.5 million new cases of CL, and a numerous population is at risk in the endemic areas. Despite its increasing worldwide incidence, it is one of the so-called neglected tropical diseases. Furthermore, this review provides an overview of the existing knowledge of the host innate and acquired immune response to cutaneous species of Leishmania. The use of animal models and of in vitro studies has improved the understanding of parasite-host interplay and the complexity of immune mechanisms involved. The importance of diagnosis accuracy associated with effective patient management in CL reduction is highlighted. However, the multiple factors involved in CL epizoology associated with the unavailability of vaccines or drugs to prevent infection make difficult to formulate an effective strategy for CL control.